Rethinking Assessment Concepts in Dental Education - Mohamed El-Kishawi; Khaled Khalaf; Dana Al-Najjar; Zahra Seraj; Sausan Al Kawas (International Journal of Dentistry)
Introduction. Dental education involves teaching and assessing the acquisition of verifiable domains that require superior psychomotor, communication, and cognitive skills. Evolving technologies and methods of assessment could enhance student’s learning environment and improve tutor assessment experience. The aim of this study was to review the current body of research and evaluate the effectiveness of various methods of assessments in improving learning and performance in preclinical and clinical dental practice. Materials and Methods. A search strategy was implemented using electronic search in major databases. The following key terms, clinical skills, preclinical, dental students, and assessment, were included in the search. Two reviewers independently screened all the articles retrieved following very specific inclusion criteria. Results. The initial search generated 5371 articles and 24 articles were selected for review and data extraction. Cohen’s kappa coefficient was used to measure interrater agreement and a score of 94.7% was obtained. Conclusion. Preclinical assessment is an effective tool for promoting skills transfer to clinical phase. Early psychomotor skills assessment is valuable. It allows early intervention in the learning process and assists in effective utilization of learning resources. Technology-enhanced assessment systems allow better patient simulation, enhance learning and self-assessment experiences, and improve performance evaluation. However, these systems serve as an adjunct to conventional assessment methods. Further research should aim at calibrating and integrating these systems to optimize students learning and performance.